P01.108 Use of complementary and alternative medicine in glioma patients. (19th September 2018) - Hertler, C; Roelcke, U; Conen, K; Huber, F; Weiss, T; Hofer, S; Heese, O; Westphal, M; Roth, P; Weller, M; Eisele, G
Abstract: Background: Patients suffering from brain tumors, as other cancer patients, may rely on additional support of complementary and alternative medicine (CAM) treatment during the course of disease. However, the assessment and documentation of CAM is not necessarily part of the clinical routine in oncological consultations. Moreover, CAM comprises different agents and treatments that may vary depending on the country the patient lives. Overall, there is a lack of information on type and motivation for CAM use in glioma patients in Switzerland. Material and Methods: A multi-center cross-sectional survey analysis of CAM use in glioma patients was conducted in 3 specialized Neuro-Oncology Centers in Switzerland from 2012–2015. On the occasion of a regular consultation, a questionnaire including multiple choice questions as well as open response questions was provided to patients suffering from a glioma WHO II-IV. Results: Overall, 208 patients completed the survey. Approximately half of the patients (n=101 patients, 49 %) reported the use of CAM during the course of the disease. Patients reported the wish to contribute actively to the cancer treatment as the most important motivation for CAM use. CAM user were most likely younger patients, usually using CAM without medical supervision and without necessarily being reimbursed by the insurance company. CAM use was distributed amongst WHO grades and both genders. Conclusions: In this multi-center survey analysis conducted in Switzerland, almost half of the glioma patients reported to have used CAM during the course of the disease. This demand should be addressed by the treating physicians. An accurate documentation and counseling could improve patient care, by avoiding potential interactions with the standard treatment and by incorporation of patients' needs into therapy. Funded by the Swiss Brain Tumor Foundation